Programa “Actiludi” para mejorar la Expresión Oral en niños de 3 años de la I.E 209 Santa Ana 2016 - De La Cruz Delgado, Maribel (2017)
The research aims to demonstrate that the application of the program "ACTILUDI” is of great importance to significantly improve the oral expression in children of initial level._x000D_ The lack of good oral expression presented by 3-year-old children from the initial level of the I.E. N ° 209 "Santa Ana"._x000D_ The proposed research is applied with a quasi experimental design with a control group and an experimental group, with pre and post test. Taking place with a sample of 53 students, the "Lila" classroom being the experimental group with 27 children and the "white" classroom the control group with 26 children._x000D_ The "ACTILUDI" program was implemented, based on educational games for the improvement of oral expression in the experimental group. The results obtained were: In the control group, a score of 11.96, equivalent to 59.81% and Experimental group a score of 16.63 that equals 83.15%, demonstrating that the students of this group have managed to significantly improve the Level of lack of good oral expression.